The study evaluated arming of risk of lanslide in Hoa Binh and Son La reservoir hydropower area on the basis of analyzing high-resolution remote sensing and geographic information systems - Hung, Pham Van; Son, Pham Quang; Dung, Nguyen Van (Vietnam Journal of Earth Sciences, 2016)
Based on the analysis of high-resolution remote sensing (VNREDSat-1 and SPOT-5, Landsat-8) and geographic information system (GIS) has allowed the assessment of the status and alert landslide risk in the basin Hoa Binh and Son La hydropower reservoirs. On the reservoir basin Hoa Binh and Son La hydropower established by sliding blocks 828 large and small, the distribution of the strip runs the NW-SE: Phong Tho-Tam Duong, Than Uyen-Mu Cang Chai, Muong La-Da Bac, Tua Chua-Thuan Chau, Son La-Mai Chau and submeridian: Muong Lay-Muong Cha, Quynh Nhai-Thuan Chau. Map of landslide risk basin Hoa Binh and Son La hydropower reservoirs were constructed on the basis of 11 integrated map landslide risk analysis component by comparing pairs and spatial analysis in GIS environment. On basin reservoir Hoa Binh and Son La hydropower, the areas at risk of landslides is very low accounting for  4%, down 36%, average 33%, high 24% and very high 3% of the natural area of the study area. The areas with landslide risk is very high and higher should be focused on prevention measures, prevention include: Phong Tho, Than Uyen, Mu Cang Chai, Muong Lay, Muong Cha, Thuan Chau, Da Bac, Mai Chau and Son La town.ReferencesGuzzetti F., Carrara A., Cardinali M., Reichenbach et P., 1999: Landslide hazard evaluation: a review of current techniques and their application in a multi-scale study, Central Italy. Geomorphology, vol. 31, no 1-4, p. 181-216. Trần Trọng Huệ (chủ biên), 2000: Nghiên cứu đánh giá trượt lở mép hồ Hòa Bình, đề xuất các giải pháp phòng tránh. Báo cáo tổng kết đề tài, Viện Địa chất, Hà Nội. Trần Trọng Huệ (chủ biên), 2003: Nghiên cứu đánh giá các loại hình tai biến địa chất trên lãnh thổ Việt Nam và các giải pháp phòng tránh (giai đoạn 2 - các tỉnh miền núi phía Bắc). Báo cáo tổng kết đề tài, Viện Địa chất, Hà Nội. Lomtadze V.Đ., 1982: Địa chất công trình- địa chất động lực công trình. Bản dịch tiếng Việt của Phạm Xuân và nnk. Nxb. ĐH&THCN, Hà Nội. Saaty, Thomas L., 1994: Fundamentals of decision making and priority theory with analytic hierarchy process. Pittsburgh: RWS publications, 527 p. Trần Anh Tuấn, Nguyễn Tứ Dần, 2012: Nghiên cứu nhạy cảm và phân vùng nguy cơ trượt - lở đất khu vực hồ thủy điện Hòa Bình - Sơn La  theo phương pháp phân tích cấp bậc Saaty. Tạp chí Các Khoa học về Trái Đất, T.34, (3), tr. 223 -232. Đào Văn Thịnh (chủ biên), 2005: Các tai biến địa chất ở Tây Bắc Bộ. Báo cáo tổng kết đề tài, Cục Địa chất và Khoáng sản Việt Nam, Hà Nội. Nguyễn Trọng Yêm (chủ biên), 2006: Nghiên cứu thành lập bản đồ tai biến thiên nhiên lãnh thổ Việt Nam tỷ lệ 1:500.000. Báo cáo tổng kết đề tài mã số KC-08-01, Viện Địa chất, Hà Nội.